Poverty Reduction in Perspective of Public Service Reform: A Study on Legal and Social Analysis (Case of Sragen, Indonesia) - Jhody, Puguh Setyawan (JILS (Journal of Indonesian Legal Studies), 2017)
The problem of poverty is a complex multidimensional problem as a general social phenomenon that requires steps to overcome, systematically, integrated, and comprehensive. These efforts are used to reduce the burden and fulfill the basic rights of citizens properly to bring about a prosperous society. Current poverty reduction models tend to be misplaced, bureaucratic, weak monitoring and evaluation, overlapping authority, and budgetary wastage. Therefore, the Government of Sragen Regency established the Poverty Reduction Service Unit (UPT-PK). The unit is an integrated cross-sectoral service unit in poverty alleviation with the aim of simplifying and facilitating the poor to access government programs that are for them. The focus of research on the model of poverty alleviation services based on education, health, socio-economic, and data integrity and its implementation constraints. The research used qualitative research approach of law with type of sociological juridical research using analysis of interactive analysis models. Poverty reduction is the policy of the Government of Sragen Regency in realizing the welfare of the community.